2013
DOI: 10.1126/science.1226767
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Triggers Social Aversion via Glucocorticoid Receptor in Dopaminoceptive Neurons

Abstract: Repeated traumatic events induce long-lasting behavioral changes that are key to organism adaptation and that affect cognitive, emotional, and social behaviors. Rodents subjected to repeated instances of aggression develop enduring social aversion and increased anxiety. Such repeated aggressions trigger a stress response, resulting in glucocorticoid release and activation of the ascending dopamine (DA) system. We bred mice with selective inactivation of the gene encoding the glucocorticoid receptor (GR) along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
171
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(191 citation statements)
references
References 38 publications
15
171
0
5
Order By: Relevance
“…Increased DA neuron activity is a prerequisite for the subsequent behavioral manifestations of stress outcomes. [24][25][26][27] Indeed, pharmacological or optogenetic inhibition of VTA DA neurons promotes therapeutic-like effects as it reverses SD-induced social aversion and anhedonia. 24,25 Thus, VTA DA neurons are at a crossroad of nicotine's reinforcing effects and social stress-induced aversion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased DA neuron activity is a prerequisite for the subsequent behavioral manifestations of stress outcomes. [24][25][26][27] Indeed, pharmacological or optogenetic inhibition of VTA DA neurons promotes therapeutic-like effects as it reverses SD-induced social aversion and anhedonia. 24,25 Thus, VTA DA neurons are at a crossroad of nicotine's reinforcing effects and social stress-induced aversion.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Indeed, pharmacological or optogenetic inhibition of VTA DA neurons promotes therapeutic-like effects as it reverses SD-induced social aversion and anhedonia. 24,25 Thus, VTA DA neurons are at a crossroad of nicotine's reinforcing effects and social stress-induced aversion. We hypothesized that nAChRs could be a pivotal molecular target, which would orchestrate the detrimental stress-nicotine interplay at the cellular and behavioral levels.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study demonstrated that mental and physiological conditions of individuals are important in the promotion and development of cancers and changes in patient's life style could be effective in incidence of stress (Cohen et al, 2007;Mancino et al, 2011;Barik et al, 2013). Cancer cells and nerve fibers have cross-talks and thus could influence on each other.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the main reasons of cancer-related mortality in women and its rate in developing countries is annually 70% of which will occur (Haghighat S, 2012). Researchers believe that mental and physiological conditions of individuals are important in the promotion and development of cancers and changes in patient's life style could be effective in incidence of stress (Elenkov et al, 2000;Cohen et al, 2007;Barik et al, 2013). Improvement the quality of life can be effective in reduction of breast cancer patients' distress and the risk of breast cancer (Yavuzsen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, metyrapone-induced pharmacological adrenalectomy has the opposite effects (Czyrak et al, 1997). Moreover, long-term high levels of GCs under specific conditions of genetic susceptibility could exert a long-term, epigenetic control of ventral tegmental area-originated dopaminergic neurons (Niwa et al, 2013) as well as promote stress-related, dopamine-dependent adaptive changes in dopaminoceptive neurons related with emotional and social behavioural phenotypes (Barik et al, 2013), contributing to psychopathology. Furthermore, disruption of the circadian pattern of GCs' fluctuations and increased systemic GC levels in rats have been shown to increase dopamine release in the PFC possibly as a result of increased synthesis and vesicular storage, providing a mechanistic explanation for prefrontal dysfunction in bipolar and other affective disorders associated with GC dysrhythmia (Minton et al, 2009) (Figure 3).…”
Section: Enhancing Versus Attenuating Systems Of Neurotransmissionmentioning
confidence: 99%